The role of aging of astrocytes in pathogenesis of Alzheimer's disease (Experimental biology, 2017)
Alzheimer's disease (AD) is a neurodegenerative disease in elderly people and is characterized by cerebral atrophy, the accumulation of peptides of β-amyloid (Aβ) and tau protein in brain cells. It is suggested that with aging, accumulation of Aβ in the brain tissues can lead to the development of inflammatory processes and the death of nerve cells as a result of the formation of neurotoxic compounds such as reactive oxygen species, nitric oxide, pro-inflammatory cytokines. In this regard, the aim of this work was to study the effect of Aβ on the synthesis of the proinflammatory cytokine IL6 and to perform a comparative evaluation of the effect of proinflammatory cytokines TNF-α and IFN-γ on young and aging astrocytes. To elucidate these questions, methods of obtaining of a population of aging astrocytes from human fetal brain tissue, methods of incubation of astrocytes with pro-inflammatory cytokines TNF-α and IFN-γ and β-amyloid, immunofluorescence detection and superoxide anion determination in young and aging astrocytes were used. In the course of the work, it was found that aging astrocytes are more sensitive to pro-inflammatory signals than younger cells, as evidenced by increased synthesis of reactive oxygen species (superoxide anion) upon exposure to TNF-α and IFN-γ. It is also shown that the effect of Aβ leads to a significant increase in the level of proinflammatory cytokine IL-6 in aging astrocytes as compared to younger cells. Thus, increased synthesis of ROS and pro-inflammatory cytokines in aging brain cells plays a key role in the pathogenesis of Alzheimer's disease. The obtained data have an important theoretical and practical significance in the study of the pathogenesis of this disease, as well as for the development of treatment tools for age-related neurodegenerative diseases.
Keywords: astrocytes, β-amyloid, cytokines, β-galactosidase, cell aging.